2021
DOI: 10.1007/s00281-021-00863-y
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils and eosinophil-associated disorders: immunological, clinical, and molecular complexity

Abstract: Eosinophils and their mediators play a crucial role in various reactive states such as bacterial and viral infections, chronic inflammatory disorders, and certain hematologic malignancies. Depending on the underlying pathology, molecular defect(s), and the cytokine- and mediator-cascades involved, peripheral blood and tissue hypereosinophilia (HE) may develop and may lead to organ dysfunction or even organ damage which usually leads to the diagnosis of a HE syndrome (HES). In some of these patients, the etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 134 publications
0
36
0
Order By: Relevance
“…Activated platelets, EETs, and MBP contribute to thrombus formation [ 25 , 26 ]. Eosinophils are pro-inflammatory cells and can release a great number of cytokines, growth factors, and chemokines, which enhance inflammatory reactions [ 22 , 27 , 28 ]. Cytokines, including interleukin (IL)-1β, IL-2, IL-6, IL-8, and tumor necrosis factor-α, are upregulated in AD patients [ 28 31 ], and may promote AD via apoptosis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets, EETs, and MBP contribute to thrombus formation [ 25 , 26 ]. Eosinophils are pro-inflammatory cells and can release a great number of cytokines, growth factors, and chemokines, which enhance inflammatory reactions [ 22 , 27 , 28 ]. Cytokines, including interleukin (IL)-1β, IL-2, IL-6, IL-8, and tumor necrosis factor-α, are upregulated in AD patients [ 28 31 ], and may promote AD via apoptosis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the historical categorization of eosinophils as destructive cells in asthma and parasite infection, eosinophils have nuanced and complex immune regulatory roles in health and disease. 4,28,29 Studies in mice have identified that at physiological homeostasis eosinophils maintain metabolic health 30 and aid in tissue remodeling during development. 31 They have also been shown to maintain a healthy microbiome in the gut 32 and promote vascular hemostasis.…”
Section: Eosinophils In Nonallergic Diseasesmentioning
confidence: 99%
“…Dear Editor, Hypereosinophilic syndrome (HES) is characterized by peripheral eosinophilia (eosinophils, ≥1500/μL), eosinophil-associated end-organ damage, and no underlying causative disorders such as infections, allergic diseases, bullous diseases (e.g., bullous pemphigoid), pulmonary diseases, malignant neoplasms, and collagen diseases including eosinophilic granulomatosis with polyangiitis (EGPA). [1][2][3][4] We present the very rare case of a Japanese patient with eosinophilic vasculitis (EoV) as a cutaneous manifestation of idiopathic HES.…”
Section: Eosinophilic Vasculitis As a Manifestation Of Idiopathic Hyp...mentioning
confidence: 99%
“…LETTER TO THE EDITOR Subtypes of HES include idiopathic, primary (or neoplastic), and secondary (or reactive) forms. [1][2][3] EoV as a manifestation of HES can be distinguished from primary systemic vasculitides such as EGPA. EGPA is a systemic eosinophilic, granulomatous ANCA-associated vasculitis affecting small-to medium-sized vessels in individuals with asthma (and/or allergic rhinitis), and peripheral eosinophilia.…”
Section: E141mentioning
confidence: 99%